An Interactive Leaming On AC Power Transformer - Abdul Kadir, Aida Fazliana; Ab Aziz , Nur Hakimah; Jatu, Gabriel (2005)
The Information Technology (IT) era has pushed the students and the teachers especially, to up to date their level of knowledge through modern style of education, which often be called, Computer Aided Education (CAE). Here, Alternating Current Power Transformer as one of the most fundamental auxiliary in Electrical Engineering is being explored theoretically, in order to come out with the adequate theoretical knowledge to be implemented into the IT based system which is called an "Interactive Learning System". The objectives of this project are to develop an interactive learning system for AC Power Transformer and to design the interactivity of the system by following the principles of multimedia design. This project will be developed with the Macromedia Flash software. The end user of this system will be experiencing a different method in learning the AC Power Transformer.